(untitled) (Scientific journal of the Fergana State University, 2026)
There are various ways to improve wheat grain quality, the main one being the selection of varieties with high baking value. This article presents a PCR analysis of NAM-1 genes responsible for protein content in landrace wheat varieties of Uzbekistan using SNP markers. In the study, PCR products were successfully obtained from 20 samples of landrace wheat varieties using specific primers NAM-A-1, NAM-B-1, and NAM-D-1. This indicates the high quality of the genomic DNA used in this study.